The Effect Of Work Ability And Work Motivation On Employee Performance At The Ulu Musi Sub-District Office, Empat Lawang Regency - Putra, Jemi; Irwanto, Tito; Abi, Yudi Irawan (Journal of Business Management, 2025)
Agencies always strive for their employees to work well so that they can achieve the best performance. To create good employee performance, of course, there are several things that must be considered by agencies, such as work ability and work motivation. The purpose of this study was to determine the effect of work ability and work motivation on employee performance at the Ulu Musi Sub-District Office, Empat Lawang Regency. The sample in this study was 33 employees at the Ulu Musi Sub-District Office, Empat Lawang Regency. Data collection using questionnaires and the analysis method used is multiple linear regression, determination test and hypothesis testing. The results of multiple linear regression calculations obtained multiple linear regression equations Y = 8.650 + 0.334X1 + 0.478X2. The coefficient of determination of the Adjusted R square value is 0.455. This means that X1 (work ability), and X2 (work motivation) affect performance (Y) by 45.5% while the remaining 54.5% is influenced by other variables not examined in this study. The F test results show that the significance is 0.000 <0.05. Because the level of significance is below 0.05, it shows that together X1 (work ability) and X2 (work motivation) have a positive and significant influence together on performance (Y). Work ability has a positive and significant effect on performance because the significant value is 0.041 <0.05, work motivation has a positive and significant effect on performance because the value is 0.007 <0.05.